SUSTAINABLE DEVELOPMENT ISSUE IN THE RELOCATION POLICY AT PETERONGAN MARKET, SEMARANG CITY - Kusumaningrum, Mira Esti; Juliani, Tiya; Amri, Khairul; Silamon, Muhammad Alfan; Roshayanti, Fenny (UI Scholars Hub, 2020)
In 2015, Peterongan Market was one of the traditional markets in the city of Semarang which was widely discussed there because of its relocation according to new government sustainable development policy. This study aims to determine the social, cultural, economic, and environmental impacts of that relocation. It follows a qualitative descriptive approach using qualitative data obtained from interviews with various sources such as traders, buyers, and parking attendants, who were most directly affected, as well as field observations and literature studies from various relevant journals and newspapers. Furthermore, qualitative data analysis uses three activity streams in the form of data condensation, presentation, and conclusions. The results of the study show that the environmental aspects of the new market look dirty because it has not been matched by adequate relocation preparations for traders. On the economic side, the lack of preparation of the proposed locations that are more feasible and accessible to buyers will likely cause a loss in trader income. From a sociocultural perspective, the lack of comprehensive justice in the policy has lost profits for traders and buyers even before they have moved. If the policy is balanced with better preparation, the market environment will look neater, cleaner, and more secure. The proposal to relocate the market is an appropriate strategy for supporting sustainable development in the city, but it must be accompanied by better preparations so that it is easy to socialize and is not rejected by the recipient of the policy.